Development of future elementary school teachers' professional self-education readiness through interactive teaching methods - Kenesbekova, Saltanat; Mukhametzhanova, Aigul; Kussainova, Marzhangul; Zhanbyrbayeva, Sayan; Alipbayeva, Laura (Journal of Education and e-Learning Research, 2024)
A modern specialist's ability to self-educate is a valuable professional quality. Education has been given the essential responsibility to develop the learners' readiness for self-education (RSE). However, university students experience difficulties organizing and implementing self-educational activities. The study's goal is to investigate the development of students' RSE and the impact of interactive training methods (ITMs) on ensuring the development of self-education skills in future elementary school (FES) teachers. The study used a pre- and post-test design for FES teachers' readiness for self-education (RSE). The study involved 240 learners at E. Buketov Karaganda University, Karaganda, Kazakhstan. The study found that university students experienced difficulties in organizing and implementing self-educational activities. The findings revealed that using integrative teaching methods increased students' readiness for self-education which is a significant improvement over traditional methods. This paper contributes to the methodological potential of university education by providing an innovative approach to improve university students' self-education preparation.